The Influence of Brand Awareness, Brand Association, Perceived Quality, and Brand Loyalty on Purchase Intention - Prasetia, Wawan; Hidayat, anas (Archives of Business Research, 2021)
This research aims to analyze the effect of brand awareness, brand association, perceived quality, and brand loyalty on purchase intention, and the approach of the theory of planned behavior. Respondents in this research were consumers and potential consumers who had purchased cement. This research used quantitative approach by distributing questionnaires to 200 respondents. Data were analyzed using the Structural Equation Method (SEM) with Partial Least Square. The findings of this research showed that perceived quality had no impact on purchase intention, meanwhile brand awareness, brand association, and brand loyalty had positive effect on purchase intention. In addition, brand awareness, brand association, and perceived quality had positive influence on brand loyalty.